Enhanced thermoelectric figure of merit of p-type Si0.8Ge0.2 nanostructured spark plasma sintered alloys with embedded SiO2 nanoinclusions. (15th January 2017) - Usenko, Andrey; Moskovskikh, Dmitriy; Gorshenkov, Mikhail; Voronin, Andrey; Stepashkin, Andrey; Kaloshkin, Sergey; Arkhipov, Dmitriy; Khovaylo, Vladimir
Abstract: We report on thermoelectric properties of p -type boron doped nanostructured bulk Si80 Ge20 synthesized via spark plasma technique. We demonstrate that the presence of a limited amount of nanometer-sized SiO2 inclusions, resulting from the oxidation during processing stages is an effective way to further thermal conductivity reduction in the nanostructured Si80 Ge20 alloys. Significant reduction of thermal conductivity and high values of Seebeck coefficient allowed us to reach a peak ZT value of about 0.72 at 800 °C in boron doped Si80 Ge20 . Graphical abstract: